2009
DOI: 10.1074/jbc.m808747200
|View full text |Cite
|
Sign up to set email alerts
|

FGF15/FGFR4 Integrates Growth Factor Signaling with Hepatic Bile Acid Metabolism and Insulin Action

Abstract: The current studies show FGF15 signaling decreases hepatic forkhead transcription factor 1 (FoxO1) activity through phosphatidylinositol (PI) 3-kinase-dependent phosphorylation. The bile acid receptor FXR (farnesoid X receptor) activates expression of fibroblast growth factor (FGF) 15 in the intestine, which acts through hepatic FGFR4 to suppress cholesterol-7␣ hydroxylase (CYP7A1) and limit bile acid production. Because FoxO1 activity and CYP7A1 gene expression are both increased by fasting, we hypothesized C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 72 publications
1
78
1
Order By: Relevance
“…The second mechanism involves the conversion of cholesterol into bile acids through a series of enzymatic reactions, in which Cyp7a1 encodes the rate-limiting enzyme (53,54). All 3 genes -Abcg5, Abcg8, and Cyp7a1 -are reportedly regulated by hepatic FoxO1 (55)(56)(57)(58). Moreover, we have previously reported that an additional enzyme involved in bile acid synthesis, Cyp8b1, is a FoxO1 target (10).…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism involves the conversion of cholesterol into bile acids through a series of enzymatic reactions, in which Cyp7a1 encodes the rate-limiting enzyme (53,54). All 3 genes -Abcg5, Abcg8, and Cyp7a1 -are reportedly regulated by hepatic FoxO1 (55)(56)(57)(58). Moreover, we have previously reported that an additional enzyme involved in bile acid synthesis, Cyp8b1, is a FoxO1 target (10).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding (physiological increase of insulin) decreased CYP7A1 mRNA by 90% compared to the fasting state in mice. The fasting induction of CYP7A1 was blunted in liver-specific FOXO1 knock-out mice (Shin and Osborne, 2009). In contrast, insulin at physiological concentrations showed dual effects on human CYP7A1 gene expression; a rapid stimulation of human CYP7A1 through FOXO1 inactivation and a late repression of CYP7A1 mediated by prolonged insulin exposure-induced SREBP-1c (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…FGF19 signaling is also involved in the regulation of glucose, lipid metabolism, and bile acid metabolism (Bhatnagar et al, 2009;Shin and Osborne, 2009). Administration of human FGF19 or transgenic expression of human FGF19 in mice enhanced energy expenditure and fatty acid oxidation and reduced hepatic, serum triglyceride, and glucose levels (Tomlinson et al, 2002;Fu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%